Anaerobic digestion of food waste – Challenges and opportunities. (January 2018) - Xu, Fuqing; Li, Yangyang; Ge, Xumeng; Yang, Liangcheng; Li, Yebo
Highlights: AD of food waste is promising but has not yet been widely applied. The quantity, composition, and CH4 potential of different food wastes are summarized. Co-digestion with animal manure and sewage sludge are practical options. Micronutrients supplementation are needed for food waste only digesters. Control of foaming and improved process design are required. Abstract: The disposal of large amounts of food waste has caused significant environmental pollution and financial costs globally. Compared with traditional disposal methods (i.e., landfilling, incineration, and composting), anaerobic digestion (AD) is a promising technology for food waste management, but has not yet been fully applied due to a few technical and social challenges. This paper summarizes the quantity, composition, and methane potential of various types of food waste. Recent research on different strategies to enhance AD of food waste, including co-digestion, addition of micronutrients, control of foaming, and process design, is discussed. It is envisaged that AD of food waste could be combined with an existing AD facility or be integrated with the production of value-added products to reduce costs and increase revenue. Further understanding of the fundamental biological and physicochemical processes in AD is required to improve the technology.